ECONOMIC FEASIBILITY AND MONTE CARLO SIMULATION IN A NURSERY FOR NATIVE FOREST SPECIES SEEDLING PRODUCTION IN THE SOUTHWEST REGION OF BAHIA, BRAZIL - Benedito, Débora Caroline Defensor; Coelho, Kemele Cristina; Novaes, Adalberto Brito de; Cipriani, Vânia Beatriz; Aguiar, Natália Saudade de; Silva, Liniker Fernandes da (Floresta, 2025)
Forest seedling nurseries are regarded as projects that require high initial investment, therefore, it is necessary to assess the economic viability and the risks that may influence results. This study aimed to analyze the viability of implementing a forest nursery of native species seedlings in Vitória da Conquista, BA, Brazil, aiming at meeting regional demand. The study was carried out by simulating an implementation project of a native seedling nursery, with productive capacity of 415,904 seedlings per year. A planning horizon of 10 years and an interest rate of 8% per year was used to analyze the economic feasibility of the cash flow of the enterprise. The following economic viability indicators were calculated with Microsoft Excel®: Net Present Value (NPV); Internal Rate of Return (IRT); Benefit Cost Ratio (B/CR); Equivalent Periodic Value (EPV); and Average Production Costs (APC). Excel® was also used to perform a Monte Carlo simulation for risk assessment, which consisted of running 10,000 iterations. Input variables were the success rate of seedling production, seedling selling price and workforce cost. NPV was the output variable. The results indicated the viability of all economic indicators calculated. Monte Carlo simulation indicated a profitable probability of 82.46%. Economic evaluation and risk assessment pointed to the viability of establishing a nursery of native forest species seedlings in southwest Bahia.